1999
DOI: 10.1097/00008483-199911000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Participation Rates at Outpatient Cardiac Rehabilitation Programs in Victoria, Australia

Abstract: Despite a comprehensive network of CR programs in Victoria, they are used on average by only a minority of eligible patients. Further work is required to determine barriers to participation to develop strategies to increase participation rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
78
0
1

Year Published

2001
2001
2011
2011

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(83 citation statements)
references
References 9 publications
4
78
0
1
Order By: Relevance
“…Surveys in the UK show low levels of patient participation (14-43% after myocardial infarction) with similarly low attendance reported in Australia, 30 France, 31 New Zealand 32 and the USA. [33][34][35] Low patient participation is a consequence of low levels of provision, referral and invitation, and of poor uptake by patients.…”
Section: Uptake Of Cardiac Rehabilitationmentioning
confidence: 90%
“…Surveys in the UK show low levels of patient participation (14-43% after myocardial infarction) with similarly low attendance reported in Australia, 30 France, 31 New Zealand 32 and the USA. [33][34][35] Low patient participation is a consequence of low levels of provision, referral and invitation, and of poor uptake by patients.…”
Section: Uptake Of Cardiac Rehabilitationmentioning
confidence: 90%
“…Surveys from the UK show levels of participation between 14 and 43%. 7,[36][37][38][39] Similarly low uptake rates are reported from Australia, 40 New Zealand, 41 the USA [42][43][44] and France. 45 Of those patients who do attend hospital CR, the drop-out rates from exercise programmes generally range from 20% in the first 3 months to 50% at 6 months to 1 year, but can be as high as 87% by 1 year.…”
Section: Overall Uptake Ratesmentioning
confidence: 93%
“…Application of CR schedules to patients with heart failure or following cardiac procedures has gained increasing acceptance as their benefits and safety are documented. Despite its potential clinical and psychological benefits, among all survivors following myocardial infarction or cardiac interventions, only 11% to 20% completely participate in CR programs [1], and this participation rate is dramatically lower among women than men [2,3]. It was suggested that women with coronary artery disease, enrollment in CR programs is much less than expected based on their prevalence of cardiac events [4].…”
Section: Introductionmentioning
confidence: 99%